(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
Bankura district is located in the western tip of West Bengal. The climate of this district is mainly harsh and dry. Seemingly festivals add another dimension to this ordinary public life and it is needless to say that the festival creates a new excitement in the life of the masses. The diverse folk festivals here make the district special. Despite the great adversity of nature, the people of Bankura overcame the hardships and floated in the tide of folk festivals. Festivals are also filled with joy, dance, and many more folk rituals. The contribution of these folk festivals is very important for rural public life. There are a lots of folk festivals are found in the Bankura district. The folk festivals here have created a unique cultural atmosphere in their diversity and characteristics. It is difficult to record it in a single effort. Hence, this article highlights some of the most prevalent and popular folk festivals of Bankura district. Among those, the coexistence of nature and tradition can be observed through the popular folk festivals of the tribal community, such as Baram, Karam, Bejabendha, Saharai, Chhata Parab, Baha Parab etc. On the other hand, the popular folk festivals of other local communities, such as Shivagajan, Dharmagajan, Jhapan, Dussehra, Shial-Shakuni Puja, Bhadu Parab, Tusu Parab, Indparab etc. makes an indescribably beautiful co-existence of devotees, devotion, God, and folklore make the mind happy with natural thoughts. In several pujas, the devotion of the devotees to the purpose of the Lord is also unparalleled. Nirambu upobas, Dandi khata, Dhuno porano, Agune jhap, Hul forano, Banfore, Hotye etc. Besides the religious rituals, the sky is resounding with the singing of God’s name. As an accompaniment to folk festivals, they acquire another dimension with dance, song, and music.